Ownership Structure, Business Group Affiliation, Listing Status, and Earnings Management: Evidence from Korea* - Kim, Jeong‐Bon; Yi, Cheong H. (Contemporary Accounting Research, 2006)
Using a large sample of both publicly traded and privately held firms in South Korea (hereafter “Korea”), we investigate whether, and how, the deviation of controlling shareholders' control from ownership, business group affiliation, and listing status differentially affect the extent of earnings management. Our study yields three major findings. First, we find that as the control‐ownership disparity becomes larger, controlling shareholders tend to engage more in opportunistic earnings management to hide their behavior and avoid adverse consequences such as disciplinary action. The result of our full‐model regression reveals that an increase in the control‐ownership wedge by 1 percent leads to an increase in the magnitude of (unsigned) discretionary accruals by 1.3 percent of lagged total assets, ceteris paribus. Second, we find that for our full‐model regression, the magnitude of (unsigned) discretionary accruals is greater for group‐affiliated firms than for nonaffiliated firms by 0.8 percent of lagged total assets. This result suggests that business group affiliation provides controlling shareholders with more incentives and opportunities for earnings management. Finally, we find that for our full‐model regression, the magnitude of (unsigned) discretionary accruals is greater for publicly traded firms than for privately held firms by 1.2 percent of lagged total assets. This result supports the notion that stock markets create incentives for public firms to manage reported earnings to satisfy the expectations of various market participants that are often expressed in earnings numbers.